Schistosome Eggs Impair Protective Th1/Th17 Immune Responses Against Salmonella Infection - Schramm, Gabriele; Suwandi, Abdulhadi; Galeev, Alibek; Sharma, Samriti; Braun, Janin; Claes, Anne-Kathrin; Braubach, Peter; Grassl, Guntram A. (Frontiers in Immunology, 2018)
Countries with a high incidence of helminth infections are characterized by high morbidity and mortality to infections with intracellular pathogens such as Salmonella. Some patients with Salmonella-Schistosoma co-infections develop a so-called “chronic septicemic salmonellosis“, with prolonged fever and enlargement of the liver and spleen. These effects are most likely due to the overall immunoregulatory activities of schistosomes such as induction of Tregs, Bregs, alternatively activated macrophages, and degradation of antibodies. However, detailed underlying mechanisms are not very well investigated. Here, we show that intraperitoneal application of live Schistosoma mansoni eggs prior to infection with Salmonella Typhimurium in mice leads to an impairment of IFN-γ and IL-17 responses together with a higher bacterial load compared to Salmonella infection alone. S. mansoni eggs were found in granulomas in the visceral peritoneum attached to the colon. Immunohistological staining revealed IPSE/alpha-1, a glycoprotein secreted from live schistosome eggs, and recruited basophils around the eggs. Noteworthy, IPSE/alpha-1 is known to trigger IL-4 and IL-13 release from basophils which in turn is known to suppress Th1/Th17 responses. Therefore, our data support a mechanism of how schistosomes impair a protective immune response against Salmonella infection and increase our understanding of helminth-bacterial co-infections.